Morphological and Molecular Characterization of Soybean (Glycine max L.) Genotypes undre Salt Stress (Annals of Bangladesh Agriculture, 2021)
Three advanced lines (SB02, SB05, SB07) along with one tolerant (Lokon) and one susceptible check (Asswt) of soybean (Glycine max L.) were assessed for salt tolerance in terms of morpho-physiological traits and molecular markers (SSR). The experiment was conducted at seedling stage with four salinity treatments namely 0, 8, 12 and 16 dSm-1 following Completely Randomized design. All the genotypes displayed considerable reduction in their morphological traits, least affecting the tolerant one. None of the genotypes were survived at 12 and 16 dSm-1 stress condition. Among the lines tested, SB-02 and SB-05 were identified as salt tolerant at 8 dSm-1 based on salinity susceptibility index (SSI) scoring. These genotypes suffered less in reduction of leaf chlorophyll content (SPAD) and increase of Na+/K+ than the susceptible genotypes. For all the traits viz. shoot length, root length, total length, shoot fresh weiht, root fresh weight, shoot dry weight, root dry weight, total fresh weight, total dry weight, percent live leaves, chlorophyll content and Na+/K+ ratio, the phenotypic coefficient of variation (PCV) was higher than that of genotypic coefficient of variation (GCV). All the traits studied showed medium to high heritability ranging between 43.81% (SPAD) to 96.65% (shoot length). The genotypes were grouped into two clusters considering both Euclidian distance and Unweighted Pair Group Method with Arithmetic Mean analysis. Lokon, SB-02 and SB-05 are on the same cluster as tolerant, and SB-7 and Asset on the other as susceptible to salt stress. The molecular pattern using by SSR marker displayed an average number of 3.33 alleles per locus with PIC (Polymorphism Information Content) values ranged from 0.2688 (sat_655 and satt728) to 0.7680 (sat_210). The highest gene diversity was observed in sat_210 and satt237 and the lowest in sat_655 and satt728 with a mean diversity of 0.5733. The genotypes Lokon, SB-02 and SB-05 could be suggested as a potential germplasm source of QTL (Quantitative Trait Loci) analysis for the development of salt tolerant soybean variety.Ann. Bangladesh Agric. (2020) 24(2): 33-46